Implementation of Technology-Based Public Service Innovation in Increasing Bureaucratic Efficiency: The Role of Education in Improving Service Performance - Gantika, Soma (Journal of English Language and Education, 2025)
This study aims to explore the application of technological innovation in public services and the role of education in improving service performance. Using a qualitative approach with a case study design, this study collected data through in-depth interviews, participant observation, and documentation to analyze the impact of technology on bureaucratic efficiency, transparency, accountability, and public satisfaction. The results showed that the implementation of technology-based systems, such as e-Procurement and e-Auction, successfully improved the efficiency of administrative processes, reduced task completion time, and increased transparency and accountability. In addition, technology-based education for government officials and increased digital literacy for the community proved important in maximizing the benefits of the technology. Better education allows government officials to adopt technology more quickly and improve service quality, while community digital literacy increases the utilization of technology-based services, which in turn increases public satisfaction. This study suggests the importance of integrating technology education into training programs for government officials and the community to ensure the success of technology implementation in public services. Further research is recommended to further examine the long-term impact of digital literacy and technology-based education in different public service sectors.